2015
DOI: 10.1120/jacmp.v16i6.5748
|View full text |Cite
|
Sign up to set email alerts
|

A method to improve dose gradient for robotic radiosurgery

Abstract: For targets with substantial volume, collimators of relatively large size are usually selected to minimize the treatment time in robotic radiosurgery. Their large penumbrae may adversely affect the dose gradient around the target. In this study, we implement and evaluate an inner‐shell planning method to increase the dose gradient and reduce dose to normal tissues. Ten patients previously treated with CyberKnife M6 system were randomly selected with the only criterion being that PTV be larger than 2 cm3. A new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Intuitionally, the optimal cone size is directly related with the size and geometric irregularity of the PTV. Considerable researches have been published [ 24 26 ], which showed that the quality of treatment plan would be improved even with simple empirical formula or mechanism. However, this issue has not been fully addressed, which could be explored potentially with the DL technique.…”
Section: Discussionmentioning
confidence: 99%
“…Intuitionally, the optimal cone size is directly related with the size and geometric irregularity of the PTV. Considerable researches have been published [ 24 26 ], which showed that the quality of treatment plan would be improved even with simple empirical formula or mechanism. However, this issue has not been fully addressed, which could be explored potentially with the DL technique.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the empirical formula for real patient cases is that the diameter of collimator should be 0.5-0.7 times the target diameter (Pöll et al 2008). For multiple collimators, the study in (Li et al (2015) proposed an improvement in dose conformity by using smaller-sized collimators to cover the outer region of the target volume. These publications enlighten the study of collimator choice.…”
Section: Discussionmentioning
confidence: 99%
“…The optimization of monitor unit (MU) was performed as follows: total MU: 90,000; max MU per beam: 500; max MU per node: 1500. This could reduce isodose lines showing up as streaks in the direction of beam entry points, and hot spots in the vicinity of the beam entry points just below the skin surface [ 11 ].…”
Section: Methodsmentioning
confidence: 99%